Claim Reserves Estimation Using Chain Ladder Method in Casualty Insurance for the Period 2010 - 2019 - Muara Lysta Sirait; Muhammad Alfarisi; Zievan Ananta Pahlevi; Maria Yus Trinity Irsan (CV Putra Publisher, 2024)
In a work environment, the presence of risk or unforeseeable events is inevitable, as employees certainly seek to get a sense of security in doing work. Therefore, insurance is responsibility to provide sense of security to employees by providing protection in the form of claim payments to employees who get accidents. To meet the claim payment, insurance companies need to prepare funds. With the chain ladder method, insurance companies can estimate how much funds must be prepared to make claim payments. This study used the secondary data from general insurance companies in the United States published by the National Association of Insurance Commissioners under the title